Physical growth pattern of school going urban adolescent girls in Bangalore city - Dhoundiyal, Manju; Prithviraj, Renuka (International Journal Of Community Medicine And Public Health, 2017)
Background: With growing prioritization on adolescent health and incorporation of adolescent component in the National programme for mother and child, it is time we develop region wise growth charts for them. The objective of the study was to assess the growth pattern of adolescent school girl’s aged 13 and 14 years old belonging to different socio-economic backgrounds using simple anthropometric measurements. Methods: A cross sectional study was carried out among 468 girl students. The sample comprised 13 and 14 year old girls studying in four schools representative of different socioeconomic backgrounds in Bangalore, Karnataka. Simple anthropometric measurement were performed and compared with WHO/IAP and ICMR reference standards. Results: The anthropometric measurements (weight, height and BMI of girls) in the four schools showed similar trends but were not comparable with the reference guidelines. Conclusions: There is a need to revise and develop regional guidelines for growth charts.